The causal approach to scalar QED via Duffin-Kemmer-Petiau equation - Lunardi, J.T.; Manzoni, L.A.; Pimentel, B.M.; Valverde, J.S. (Вопросы атомной науки и техники, 2001)
In this work we consider the scalar QED via Duffin-Kemmer-Petiau equation in the framework of Bogoliubov-Epstein-Glaser causal perturbation theory. We calculate the lowest order distributions for Compton scattering, vacuum polarization, the self energy and, by using a Ward identity, the vertex correction. The causal method provides a mathematically well defined and noneffective theory which determines, in a natural way, the propagator and the vertex of the usual effective theory.